Once upon a Campus: Lessons for Improving Quality and Productivity in Higher Education - Seymour, Daniel (Rowman & Littlefield Publishers, 1995)
The unique and controversial companion volume to Daniel Seymour's On Q places Seymour's ideas and theories within the context of a call to action. In a series of realistic case-study lessons, he reveals how colleges and universities can dramatically improve their performance by drawing upon the concepts found in systems theory, quality management, and studies of organizational behavior. Seymour's goal is to overcome the current reactive mind-set and replace it with a proactive education environment where student success is the main objective. Once Upon a Campus can be put to use as an audit tool, as a guide for readers to identify problem areas in their institutions, and as a planning resource in evaluating and implementing overall performance improvement.